The Cloud Native Attitude How the World's Best Companies Use the Cloud to Speed up, Scale up and Find Product Market Fit - Currie, Anne (SRA Books, 2025)
With expert knowledge from seasoned professionals in the field, The Cloud Native Attitude equips you with the tools, knowledge and, most importantly, the right attitude to transform your understanding of the possibilities of cutting edge cloud technology. Whether you're just starting out or looking to refine your strategy, this essential and accessible read provides the clarity you need in a complex landscape